Divergent roles for NK-2 class homeobox genes in cardiogenesis in flies and mice. - Ranganayakulu, G.; Elliott, D.A.; Harvey, R.P.; Olson, E.N. (Development, 1998)
Recent evidence suggests that cardiogenesis in organisms as diverse as insects and vertebrates is controlled by an ancient and evolutionarily conserved transcriptional pathway. In Drosophila, the NK-2 class homeobox gene tinman (tin) is expressed in cardiac and visceral mesodermal progenitors and is essential for their specification. In vertebrates, the tin homologue Nkx2-5/Csx and related genes are expressed in early cardiac and visceral mesodermal progenitors. To test for an early cardiogenic function for Nkx2-5 and to examine whether cardiogenic mechanisms are conserved, we introduced the mouse Nkx2-5 gene and various mutant and chimeric derivatives into the Drosophila germline, and tested for their ability to rescue the tin mutant phenotype. While tin itself strongly rescued both heart and visceral mesoderm, Nkx2-5 rescued only visceral mesoderm. Other vertebrate 'non-cardiac' NK-2 genes rescued neither. We mapped the cardiogenic domain of tin to a unique region at its N terminus and, when transferred to Nkx2-5, this region conferred a strong ability to rescue heart. Thus, the cardiac and visceral mesodermal functions of NK-2 homeogenes are separable in the Drosophila assay. The results suggest that, while tin and Nkx2-5 show close functional kinship, their mode of deployment in cardiogenesis has diverged possibly because of differences in their interactions with accessory factors. The distinct cardiogenic programs in vertebrates and flies may be built upon a common and perhaps more ancient program for specification of visceral muscle.